Crypto decrypted : debunking myths, understanding breakthroughs, and building foundations for digital asset investing - Ryan, Jake (Financial advisor); Diorio, James M., Jr (Ascent Audio, 2023)
"Break through your ""crypto curiosity"" and uncover why blockchain innovation will revolutionize our economy, culture, and the future of investing-as well as how to navigate it safely. Between the booms, crashes, jargon, and flashy memes, blockchain technology and digital assets have not been easy for ordinary investors to understand. Hopeful investors in blockchain, digital assets, and crypto everywhere have a lengthy list of questions-and the list keeps getting longer and more nuanced. But who do they turn to for answers? In Crypto Decrypted, Tradecraft Capital's Jake Ryan and James Diorio decrypt a new world that is hidden in plain view, accessible currently to folks ""in the know."" This book is for anyone who finds themselves lost in the blockchain babble, exploring and explaining not only how to participate, but the often overlooked reasons why this new technology is relevant to every human being. Ryan and Diorio debunk common myths, clarify major breakthroughs that are often disregarded, and provide easy-to-understand answers for both crypto newbies and blockchain enthusiasts, so they can move beyond the short-term to explore what great opportunities lie ahead for blockchain technologies while providing approaches to investing more safely and soundly so that you too can profit from this technological revolution."